DESIGNING INSTRUCTIONAL MATERIALS FOR TEACHING AND LEARNING WRITING RECOUNT TEXT THROUGH EDMODO PLATFORM - Abisay, Merry Elisabeth Elsina; Rahayu, Apriliaswati (Journal of English Education Program, 2021)
This research aims to design instructional materials for teaching and learning writing recount text through the Edmodo platform to tenth-grade students of SMA Kristen Abdi Wacana Pontianak. This instructional material was designed based on the teacher's interview, analysis of the current syllabus, and the English textbook. The researcher applied ADDIE as the research model. In this research, the researcher only implemented three phases which are analyzing, designing, and developing (ADD) without implementing and evaluating phase because of time limitation. The materials and tasks were indicated the teaching and learning focus only on writing recount text. This instructional was designed to include learning through digital learning media. Thus, some of the materials and tasks were provided on the Edmodo platform. The main structures of the instructional are the books' cover, preface, syllabus, basic competence and indicator competence, learning goals, material, and task. The researcher used expert validation to make sure that the material was usable. It revealed that the interpretation result of the product was very good. Besides, these instructional materials which were designed indicate that it is workable as the teaching materials in SMA Kristen Abdi Wacana Pontianak.